Recent Advances in Biochemical Pathways : Implication for Drug Development and Therapeutics A Review - Mohammed Ibrahim Anwer; Noori Taha Khalaf; Hiba Rafid Kamal; Sana Abdalelah Abdalmawjood (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Biochemical pathways are the complex pathways of chemical reactions vital to maintain cellular homeostasis, control metabolism and modulate responses to physiological stimuli. Recent developments in the omics technologies, gene editing tools, and systems biology have significantly deepened our understanding of these pathways, changing the scientific paradigm from linear reactions to complex and interrelated regulatory networks. This review examines the changing face of metabolic and signaling pathways including but not limited to glycolysis, TCA cycle, MAPK, PI3K/AKT and JAK/STAT and their role in health and disease. Particular attention is paid to pathway analysis innovations, including CRISPR/Cas9, single-cell and spatial transcriptomics, and computational modelling and their revolutionary effect on discovery of new drug targets and pathway specific therapeutics. In reviewing the most recent advances in cancer metabolism, immune signaling, and cross-pathway interactions, this paper emphasizes the translational promise of pathway-centric research for personalized medicine, especially in oncology, neurodegeneration, cardiovascular, and autoimmune diseases. The review attempts to bridge basic biochemical research with clinical applications, and provides a window into the manner in which pathway-based interventions are influencing the future of precision therapeutics.